Author Correction: The miR-24-3p/p130Cas: a novel axis regulating the migration and invasion of cancer cells (Scientific Reports, (2017), 7, 1, (44847), 10.1038/srep44847) - Kang, Hoin; Rho, Jun Gi; Kim, Chongtae; Tak, Hyosun; Lee, Heejin; Ji, Eunbyul; Ahn, Sojin; Shin, A. Ri; Cho, Hyun Il; Huh, Yun Hyun; Song, Woo Keun; Kim, Wook; et al. (Scientific Reports, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.